Tresno Mergo Kulino (Know Then Loved) - Hendrikus Maku; Ferdinandus Sebo (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2023)
The present article aims to discuss focus the concept of religion as well as the role of religious leaders as agents of dialogue to maintain religious harmony and tolerance. The present study applies a qualitative study by investigating several literatures related to the subject of research. The findings of the present study indicate that the concept of religion needs to be rejuvenated. In addition, religious leaders should get involved in efforts to spread moderate religious values, tolerance and peace, to practice the fiqh (theory or philosophy of Islamic law) that promotes the coexistence between religions, spreading inclusive and tolerant ideas, reducing prejudiced political movement, (5) istiqomah (steadfastness) towards the constitution in order to care for diversity, and (6) maintain a cool atmosphere. Finally, this study concludes that religious leaders have a very strategic role and task to channel positive energy to their followers so that they can collaborate to build a common ground with a solid humanistic foundation.